A call for revolution : an appeal to the young people of the world - Lama, Dalai (b, 2017)
This eloquent, impassioned manifesto is possibly the most important message The Dalai Lama can give us about the future of our world. It's his rallying cry, full of solutions for our chaotic, aggressive, divided times- no less than a call for revolution. Are we ready to hear it? Are we ready to act?
Keywords: v; Wisdom -- Buddhism. -- Religious aspects